ANALISIS PENGARUH KEPUASAN INFORMASI DAN RISIKO INVESTASI TERHADAP MINAT MAHASISWA BERINVESTASI DI BURSA EFEK INDONESIA - Ade Indriati; Abdul Wahid Mahsuni; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this study was to examine the effect of information satisfaction and the level of investment risk on student interest in investing in the Indonesia stock exchange at the Investment Gallery (GI) Faculty of Economics and Business at the Malang Islamic University (UNISMA). The sample of this research is 255 respondents by purposive sampling. This data is the primary data from the distributed questionnaires. And the method of analysis of this research is multiple linear regression. The results of this study provide simultaneously that the variables of independence, information satisfaction and investment risk have a significant effect on student interest in investing in the indonesian stock exchange. While partially information satisfaction has no effect, the investment risk variable has an effect.Keyword : analysis effect of satisfaction with investment risk information and student interest in investing in the indonesia stock exchange